Length-weight and length-length relationships for four fish species of Upper Paranaiba river basin, Brazil - Costa, Gabriela O. da [UNESP]; Nobile, Andre B. [UNESP]; Lima, Felipe P. [UNESP]; Freitas-Souza, Diogo [UNESP]; Manzano, Felipe V.; Oliveira, Claudio [UNESP] (Wiley-Blackwell, 2019)
Here the length-weight and length-length relationships of four species are provided. Fishes were collected bimonthly from December 2015 to November 2016 with sieves and trawl net, with mesh size of 0.3 cm, in eight sites from the upper Paranaiba River basin, Southeastern Brazil. Fishes were measured (cm) and weighted (0.1 g) still in the field. First record of LWR and LLR are presented for three and four species, respectively.